2017
DOI: 10.1007/s13197-017-2794-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of brewing conditions on antioxidant properties of rosehip tea beverage: study by response surface methodology

Abstract: The aim of this study was to investigate the effects of brewing conditions (infusion time and temperature) on the antioxidant properties of rosehip tea beverage. The ascorbic acid content, total phenolic content (TPC), and ferric reducing antioxidant power (FRAP) of rosehip tea beverage were analysed. A two-factor and three-level central composite design was applied to evaluate the effects of the variables on the responses. The best quadratic models were obtained for all responses. The generated models were va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
2
16
2
6
Order By: Relevance
“…As shown, these independent variables impacted all the responses, however, the decoction time showed the most significant effects. Accordingly, it has been reported that the infusion time was an impactful factor affecting TPC, FRAP and ascorbic acid content of Dog rose (Ilyasoğlu & Arpa, 2017). The increase of decoction time induced an increase in TPC, TFC, DPPH radical scavenging, FRAP, and ascorbic acid to reach the maximum at 11–13 min.…”
Section: Resultsmentioning
confidence: 99%
“…As shown, these independent variables impacted all the responses, however, the decoction time showed the most significant effects. Accordingly, it has been reported that the infusion time was an impactful factor affecting TPC, FRAP and ascorbic acid content of Dog rose (Ilyasoğlu & Arpa, 2017). The increase of decoction time induced an increase in TPC, TFC, DPPH radical scavenging, FRAP, and ascorbic acid to reach the maximum at 11–13 min.…”
Section: Resultsmentioning
confidence: 99%
“…Herbal teas are prepared as infusions by brewing the dry plants with hot water or dipping tea bags into the water for a specified time (2–10 min). Based on the preparation method, the biological activity and phenolic content of herbal teas change depending on several parameters such as brewing time and temperature (İlyasoğlu & Arpa, 2017; Irakli et al., 2018; Yildirim et al., 2017). The infusion parameters should be selected based on the phytochemical profile and physical structure of the plants of interests.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the conditions for preparing herbal tea with a high content of bioactive compounds are specific to target plant material. For example, to extract the bioactive compounds, the best conditions were reported as 6–8 min at 84°C–86°C for rosehip tea (İlyasoğlu & Arpa, 2017), 5.4 min at 64°C for a tea composed of rosehip and hibiscus (Eroğlu et al., 2018), and 10 min at 99.8°C for mountain tea (Irakli et al., 2018). The hot water extraction technique has been applied in many forms throughout the history to extract the bioactive components of herbs into the solutions.…”
Section: Introductionmentioning
confidence: 99%
“…These bushes originated in East Asia, but they were brought west to Europe and America. It has grown in popularity due to its many beneficial effects, including its antioxidant properties from vitamin C and its polyphenol content, which includes tannins, anthocyanins, flavonoids, and phenolic acids [244,245]. The polyphenols found in teas are primarily catechins, the most well-known being EGCG, the primary flavonoid in green tea, which has anti-inflammatory and antioxidant properties.…”
Section: Tea Polyphenolsmentioning
confidence: 99%